PERANAN MAJELIS TAKLIM DALAM PENANAMAN NILAI-NILAI ISLAM DI KECAMATAN LUBUKLINGGAU TIMUR II KOTA LUBUKLINGGAU - Nurlila Kamsi (Manthiq, 2017)
Abstract: This study  aimed to  describe the  activities  of Islamic  study  groups  in  east  Lubuklinggau   II in implementing Islamic  value.  To describe Islamic  values   to the  Islamic  study groups  , and  to describe the implementation or actualization of Islamic  values  congregation during  informal  Council  in District II East Lubuklinggau.  This research used  qualitative  descriptive approach. In obtaining  the  data,  the  authors used observation, interviews, checklists, and  documentation. The  results  of this research indicated that  during informal  activities  in the  District Assembly  east  Lubuklinggau  II in planting  the  values  of Islam  are:  Islamic Teaching  (pengajian) regularly carried out once a week, comemoration great day in Islam (PHBI), Conducting and Training the dead bodies in Islamic ways, Conducting for reading Al-Barzanji, held a tambourine exercises, visits to orphanages, Islamic Centre  and  visit sick members of the congregation, held holding Tasbih prayer beads, and  tadarus Al-Qur’an. Islamic values  are applied  to the Islamic study groups  in east  Lubuklinggau  II in faith, Islam, charity, piety, sincerity,  trust, gratitude, patience, friendship, brotherhood, equality,  fair, well thought,  humble, a promise, gracefully, trustworthy,  officer, thrift, and kindness. Implementasi or actualizing values  of Islamic  congregation during  informal  Council  in District II East Lubuklinggau  Lubuklinggau  been done  properly,  pilgrims have  solid faith and  piety, the  faith of the  pilgrims have  a good  life and  gave birth to a sincere attitude  in addition  they  also  have  good  morals  in dealing  with  beings  Islam.  In applying  the concept of Islamic values associated with human pilgrims informal gatherings Eastern District of Lubuklinggau II Lubuklinggau  often  stay in touch,  keep  the fraternity (brotherhood Islamiyah),  was  equal  or equal  before God, to be just, kind thought,  humble, just a promise, gracefully, trustworthy,  officers, safe and generous.